2011
DOI: 10.1177/0907568210386252
|View full text |Cite
|
Sign up to set email alerts
|

Redefining participation? On the positioning of children in Swedish welfare benefits appeals

Abstract: This article deals with the representation of children in the Swedish welfare state, and particularly how children and parents living in economic hardship are positioned in issues regarding financial aid. According to Article 12 in the UNCRC, children have a right to be heard 'in any judicial and administrative proceedings affecting the child'. However, children are not participants in processes concerning welfare benefits, despite the effect that the outcome of these processes may have on children's everyday … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…However, Swedish studies show that the SA administration is marked by adult centredness. This means that adults are regarded as the main recipients and they are thus the focal point of investigations and interventions (Heimer & Palme, 2015), and empirical studies show that investigations into the needs of children are rarely made visible (Bruno, 2018;Fernqvist, 2011). Furthermore, researchers have suggested that the increased emphasis on activation, in particular when applied as workfare (i.e.…”
Section: Swedish Social Assist Ance From the International Perspectivementioning
confidence: 99%
“…However, Swedish studies show that the SA administration is marked by adult centredness. This means that adults are regarded as the main recipients and they are thus the focal point of investigations and interventions (Heimer & Palme, 2015), and empirical studies show that investigations into the needs of children are rarely made visible (Bruno, 2018;Fernqvist, 2011). Furthermore, researchers have suggested that the increased emphasis on activation, in particular when applied as workfare (i.e.…”
Section: Swedish Social Assist Ance From the International Perspectivementioning
confidence: 99%
“…Nevertheless, the results of the four sub-studies (Bruno, 2015(Bruno, , 2017Eriksson et al, 2013) suggest that patriarchy, gender inequality or male privilege are insufficient as an explanation as to why the troubling (stalking, harassment, abuse) persists after separation, and that other structuring categories also are important. The analysis takes a double view of children in line with the sociology of childhood, as both competent actors with a right to participation and vulnerable subjects in relation to adults and with rights to protection and provision (Eriksson & Näsman, 2008;Fernqvist, 2011). The key concept of familialisation was coined by the Finnish childhood sociologist Leena Alanen (1994) in order to describe the tendency to naturalise the subjugation of children in the family, this being the child's only natural platform to access resources.…”
Section: The Studymentioning
confidence: 99%
“…Children are not involved in economic production and if they are given any attention at all in this sphere it is as an economic burden for whom the parents must provide. However, the UN Convention on the Rights of the Child states that they have the right to have their needs taken into consideration and a right to participation in all matters that concern them (Fernqvist, 2011). While the last decade has seen a dramatic increase in the attention given to the position of children being exposed to physical violence from a parent (or another adult) (Eriksson, 2011) one of my conclusions is that there is complete silence regarding children's exposure to the financial abuse of one parent towards the other (Bruno, 2017).…”
Section: Familialisationmentioning
confidence: 99%
“…The government commission of inquiry that produced the corporal punishment ban also discussed children's right to voice and made far-reaching recommendations with regard to children's participatory rights in both family disputes and in child protection, which indicates a special national discourse in this area. In spite of Sweden being a likely case where children's right to voice should have been consciously strengthened, studies on children's participation in Sweden present a puzzle: CRC has apparently had very little impact on the rights of children to participate in proceedings that directly concern them (Höjer and Röbäck, 2007; Östberg, 2010; Mattsson, 2002; Eriksson and Näsman, 2011; Fernqvist, 2011). The CRC's lack of impact indicates that the implementation of children's right to voice encounters important obstacles.…”
Section: Introductionmentioning
confidence: 99%